2019
DOI: 10.2337/dc18-2578
|View full text |Cite
|
Sign up to set email alerts
|

Use of Plasma Fragments of Propeptides of Type III, V, and VI Procollagen for the Detection of Liver Fibrosis in Type 2 Diabetes

Abstract: OBJECTIVE This study assessed the utility of plasma fragments of propeptides of type III (PRO-C3), V (PRO-C5), and VI (PRO-C6) procollagen for the detection of liver fibrosis in patients with type 2 diabetes mellitus (T2DM). RESEARCH DESIGN AND METHODS Patients with T2DM (n = 191) underwent an oral glucose tolerance test, a liver 1H-MRS, and a liver biopsy when indicated. PRO-C3, PRO-C5, and PRO-C6 were blindly assessed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(61 citation statements)
references
References 15 publications
3
56
0
2
Order By: Relevance
“…Future studies must develop algorithms in this setting. This is also our own personal experience in patients recruited in diabetes clinics . A recent study compared several plasma biomarkers and diagnostic panels in 213 patients with T2DM not recruited from hepatology clinics .…”
Section: The Challenge Of Diagnosing Nash In Patients With T2dmmentioning
confidence: 75%
See 1 more Smart Citation
“…Future studies must develop algorithms in this setting. This is also our own personal experience in patients recruited in diabetes clinics . A recent study compared several plasma biomarkers and diagnostic panels in 213 patients with T2DM not recruited from hepatology clinics .…”
Section: The Challenge Of Diagnosing Nash In Patients With T2dmmentioning
confidence: 75%
“…This is also our own personal experience in patients recruited in diabetes clinics. [23][24][25][26] A recent study compared several plasma biomarkers and diagnostic panels in 213 patients with T2DM not TA B L E 1 Potential mechanisms by which chronic hyperglycemia may play a role in NASH • Hepatic inflammation and oxidative stress with formation of hydrogen peroxide/hydroxyl radicals leading to hepatocyte lipid peroxidation. • Accelerate the production of advanced glycosylation endproducts (AGEs) and development of inflammation in Kupffer and hepatic stellate cells (both have receptors for AGE).…”
Section: The Challeng E Of D Iag Nos Ing Na S H In Patients With T2dmmentioning
confidence: 99%
“…Cytokeratin (CK) 18, an intermediate filament protein that is cleaved during cell death to CK18 M30 and CK18 M65, has been intensively investigated as a surrogate of NASH-associated liver cell damage, but a recent meta-analysis of 25 studies reported a maximum sensitivity of 0.75 for NASH diagnosis [76] and suboptimal diagnostic value was shown in T2DM [75]. The ECM turnover marker, type III procollagen, can offer a diagnostic efficacy of 0.81 and 0.88 to detect moderate and advanced liver fibrosis in T2DM, respectively [77].…”
Section: Current Biomarkers and Indicesmentioning
confidence: 99%
“…Patients with high ECM formation (and thus disease activity) progress more when compared to those with normal levels 114,115 . In addition, patients with high fibrotic levels respond better to anti‐fibrotic therapies, indicating that only patients with active progressive disease will respond to therapy targeting fibrosis formation 114,116 . Consequently, the rate of ECM turnover is important for patient stratification and treatment efficacy 117 .…”
Section: The Future—ecm Profiling For Identification Of Patient Hetermentioning
confidence: 99%